Do the Guidelines for Adolescent Preventive Services (GAPS) Facilitate Mental Health Diagnosis? - Anne M. Gadomski; Melissa B. Scribani; Nicole Krupa; Paul L. Jenkins (SAGE Publishing, 2014)
Objective: To determine if the Guidelines for Adolescent Preventive Services (GAPS) increases detection or shortens time to diagnosis of mental health (MH) disorders, particularly adolescent depression. Methods: Starting in May 1999, GAPS questionnaires were routinely administered at adolescent annual visits at 1 primary care clinic in a rural health network. Using an administrative database, we enumerated all MH diagnostic codes for outpatient visits of adolescents aged 13 to 15 years. Population based rates were derived using school enrollment data. Using time series, the rates of MH diagnoses were compared pre- and post-GAPS. Using survival analysis, the time to any MH diagnosis subsequent to index annual visits was also compared pre- and post-GAPS. Because the GAPS questionnaire includes questions for depressed mood, anhedonia, and suicidality, ICD-9-CM codes for depression and mood disorder were also analyzed separately. Results: Time series analysis included 8112 adolescents. The rate of MH diagnosis did not change pre- and post-GAPS ( P = .13). Time to any MH diagnosis was similar pre-GAPS (9.0 months) and post-GAPS (7.0 months, log rank P = .30). Time to any first diagnosis of depression or mood disorder was similar post-GAPS (12.2 months) versus pre-GAPS (11.0 months, log rank P = .34). Conclusions: Use of the GAPS was not associated with change in the rate of or time to MH diagnosis. Our results challenge the prevalent expectation that requiring mental health screening will reduce unmet need for MH treatment. Validated MH screening tools, primary care provider training, and access to MH services may also be needed but further study is required.